CO2 Leakage-Induced Contamination in Shallow Potable Aquifer and Associated Health Risk Assessment. (5th April 2018) - Kim, Chan Yeong; Han, Weon Shik; Park, Eungyu; Jeong, Jina; Xu, Tianfu
Abstract : Leakage of stored CO2 from a designated deep reservoir could contaminate overlying shallow potable aquifers by dissolution of arsenic-bearing minerals. To elucidate CO2 leakage-induced arsenic contamination, 2D multispecies reactive transport models were developed and CO2 leakage processes were simulated in the shallow groundwater aquifer. Throughout a series of numerical simulations, it was revealed that the movement of leaked CO2 was primarily governed by local flow fields within the shallow potable aquifer. The induced low-pH plume caused dissolution of aquifer minerals and sequentially increased permeabilities of the aquifer; in particular, the most drastic increase in permeability appeared at the rear margin of CO2 plume where two different types of groundwater mixed. The distribution of total arsenic (∑ As) plume was similar to the one for the arsenopyrite dissolution. The breakthrough curve of∑ As monitored at the municipal well was utilized to quantify the human health risk. In addition, sensitivity studies were conducted with different sorption rates of arsenic species, CO2 leakage rates, and horizontal permeability in the aquifer. In conclusion, the human health risk was influenced by the shape of∑ As plume, which was, in turn, affected by the characteristics of CO2 plume behavior such as horizontal permeability and CO2 leakage rate.